The Effectiveness of the Use of Acupressure Therapy on Reducing the Pain Scale of Gout Arthritis in the Elderly at the Guna Budi Bakti Foundation Nursing Home - Krisman Harapan Ziliwu; Fitri Kristianis Zalukhu; Mhd Luthfi Rifai; Desman Hosada Halawa; Mesy Gultom; Elis Anggeria (Universitas STRADA Indonesia, 2021)
This study was conducted to determine the effectiveness of the use of acupressure therapy on the scale of arthritis gout pain in the elderly. This study used a quantitative method with a quasi-experimental design with one group pre-test post-test design. The population is all elderly respondents with gout arthritis. Sampling using saturated sampling. Bivariate analysis is using the Wilcoxon test. The results showed that the majority aged 60-69 years were female. The results of the data before the intervention were that the majority of severe pain, and after the intervention, the majority of mild pain. Based on the effectiveness of the use of acupressure therapy interventions given to elderly people with gouty arthritis pain, the sig (2-tailed) value was 0.00, meaning that there was a difference in pain before and after acupressure therapy.